Perlindungan Hukum terhadap Peserta Lelang Online di Media Sosial Instagram - Anggun Pulumoduyo (Lembaga Pengembangan Kinerja Dosen, 2024)
The research in this paper aims to find out more about the legal validity of online auctions via Instagram social media and how legal protection is for online auction participants on Instagram social media. The method used by the author in writing this article is a normative legal research ethod with a statutory approach. Research shows that the legal basis for carrying out online auctions via Instagram social media is Article 1320 of the Civil Code and 1338 of the Civil Code because the implementation is not submitted to an official auction house so it cannot be said to be an official auction and in implementing online auctions on Instagram social media there are weaknesses, namely in advertising goods. In the auction, information about the goods and services being sold is unclear, causing misperceptions among consumers or online auction participants on Instagram and is only based on trust. Legal protection for victims of social media online auction fraud is contained in Article 1243 of the Civil Code, Article 19 of Law Number 8 of 1999 concerning Consumer Protection, Article 28 paragraph (1) of the ITE Law, and dispute resolution is contained in Article 38 of the Law Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions.